2018
DOI: 10.2147/vhrm.s160883
|View full text |Cite
|
Sign up to set email alerts
|

Expression of phospholipase A2 receptor and IgG4 in patients with membranous nephropathy

Abstract: ObjectivesThe aims of this study were to detect the expression of M phospholipase A2 receptor (PLA2R) in the kidney tissue of patients with idiopathic membranous nephropathy (IMN), secondary membranous nephropathy (SMN), and the nonmembranous nephropathy (non-MN), to evaluate the value of PLA2R in the kidney tissue and serum anti-PLA2R antibody in the diagnosis of membranous nephropathy (MN), and to explore the relationship between PLA2R of the kidney tissue or serum anti-PLA2R antibody and clinical features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
5
7
0
Order By: Relevance
“…To our knowledge this is the first study to report significant increased renal PLA2R mRNA levels in PMN patients. Of note, this finding agrees with the enhanced PLA2R staining in biopsies from PMN patients reported in previous studies using immunohistochemistry (IHC) and/or direct immunofluorescence (DIF) [ 8 , 35 39 ]. Inversely, Hoxha et al [ 8 ] found no correlation between PLA2R staining by IHC and PLA2R mRNA levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To our knowledge this is the first study to report significant increased renal PLA2R mRNA levels in PMN patients. Of note, this finding agrees with the enhanced PLA2R staining in biopsies from PMN patients reported in previous studies using immunohistochemistry (IHC) and/or direct immunofluorescence (DIF) [ 8 , 35 39 ]. Inversely, Hoxha et al [ 8 ] found no correlation between PLA2R staining by IHC and PLA2R mRNA levels.…”
Section: Discussionsupporting
confidence: 92%
“…These significant associations between PLA2R mRNA and anti-PLA2R Ab suggest that an increase in renal PLA2R transcription could trigger in part anti-PLA2R Ab production. Likewise, previous reports showed high concordance rates between enhanced PLA2R staining and the presence of anti-PLA2R Ab [8,35,36].…”
Section: Plos Onesupporting
confidence: 71%
“…However, Rock et al [76] have noted that pemphigus vulgaris, a skin blister disease, is hallmarked by IgG4-autoantibodies in the affected skin tissue. To date, at least 13 IgG4-related autoimmune diseases have been reported including myasthenia gravis with muscle-specific kinase IgG4 antibody and idiopathic membranous nephropathy with IgG4 anti-phospholipase A2 receptor [77][78][79]. These aberrations are compatible with the observations by Aoki et al [49] that IgG4 obtained from patients with IgG4-RD bound to normal epithelial cells and exerted pathologic effects on different tissues, which are quite different from the protective effect of IgG4 antibody to damp harmful effects of immune complexes in classical autoimmune-mediated tissue damage [51,63,66,67].…”
Section: Pathologic Roles Of Igg4-autoantibodies In Certain Autoimmunmentioning
confidence: 99%
“…IgG4 antibodies undergo a process of "Fab-arm exchange" to become half-antibodies with monovalency incapable of C1q activation and with low binding affinity to FcγRII and FcγRIII resulting in non-inflammatory property [51,62,[67][68][69][70][71][72][73] Anti-allergic effect by attenuation of Th2 cytokine-mediated inflammation and immunosuppression [51,53,54,63,72] Exhibition of rheumatoid factor-like activity by Fc-Fc aggregation to resume activating complements [51,75] IgG4 obtained from IgG4-RD subjects binds to normal epithelial cells of pancreato-hepatobiliary tissues and salivary glands in vitro [49] Pathologic effects in certain autoimmune diseases including pemphigus foliaceus, muscle-specific kinase myasthenia gravis (MuSK MG) and idiopathic membranous nephropathy [76][77][78][79][80] Complement activation and hypocomplementemia in IgG4-RD with unique-pattern glycosylation [81][82][83][84][85][86]…”
Section: The Glycosylation Patterns Of Igg4 Molecule Induce Complemenmentioning
confidence: 99%
“…Previous studies have shown that circulating autoantibodies against the M-type phospholipase A2 receptor (anti-PLA2R) are detectable in 80% of IMN patients and thus serum anti-PLA2R has been widely accepted as a biomarker for clinical diagnosis of IMN [ 7 ]. The coincidence rate of serum anti-PLA2R antibody and PLA2R in kidney tissue has been demonstrated to be 100% [ 8 ]. The remainder of MN cases may be associated with the inflammatory state [ 9 ] and therefore several circulatory immune cells and inflammatory cytokines have also been suggested as biomarkers for secondary MN.…”
Section: Introductionmentioning
confidence: 99%